Analisis sikap murid terhadap penghormatan atas perbedaan dalam Pendidikan Kewarganegaraan - Sendi Fauzi Giwangsa; Zulhijjah Febriani Sitepu; Shindy Khalia; Dyna Hardyanti Sutrisno; Keisha Aulia Fadhalah (Universitas Pendidikan Indonesia, 2026)
Respect for differences is an essential character value that supports inclusive social interactions among elementary school students. However, limited evidence is available regarding how this value is developed through Civic Education learning in elementary schools. This study aims to analyze students' attitudes toward respecting differences in Civic Education learning at SD 2 Mekarmukti and identify the supporting and hindering factors in its development. This study employed a qualitative descriptive approach and collected data through observation, interviews, and documentation involving fourth-grade students and their classroom teacher. Data were analyzed using Miles and Huberman's interactive model, while triangulation ensured the trustworthiness of the findings. The findings show that students demonstrated positive attitudes toward respecting differences by accepting diversity, respecting peers from different backgrounds, and resolving conflicts through discussion and compromise. Teachers promoted tolerance through contextual learning, a democratic classroom approach, and role-playing activities, although limited instructional time and peer influence remained challenges. The findings highlight the importance of teachers' pedagogical competence, awareness of students' social context, and collaboration with families in strengthening tolerance education.